Multiplex qPCR for reliable detection and differentiation of Burkholderia mallei and Burkholderia pseudomallei - Janse Ingmar (BMC Infectious Diseases, 2013)
Abstract Background Burkholderia mallei and B. pseudomallei are two closely related species of highly virulent bacteria that can be difficult to detect. Pathogenic Burkholderia are endemic in many regions worldwide and cases of infection, sometimes brought by travelers from unsuspected regions, also occur elsewhere. Rapid, sensitive methods for identification of B. mallei and B. pseudomallei are urgently needed in the interests of patient treatment and epidemiological surveillance. Methods Signature sequences for sensitive, specific detection of pathogenic Burkholderia based on published genomes were identified and a qPCR assay was designed and validated. Results A single-reaction quadruplex qPCR assay for the detection of pathogenic Burkholderia, which includes a marker for internal control of DNA extraction and amplification, was developed. The assay permits differentiation of B. mallei and B. pseudomallei strains, and probit analysis showed a very low detection limit. Use of a multicopy signature sequence permits detection of less than 1 genome equivalent per reaction. Conclusions The new assay permits rapid detection of pathogenic Burkholderia and combines enhanced sensitivity, species differentiation, and inclusion of an internal control for both DNA extraction and PCR amplification.